The Influence of Proactive Work Behaviour, Organizational Climate, and Employee Engagement on Employee Performance at PT Sucofindo Surabaya Branch - Salim, Muhammad Nur; Swasti, Ika Korika (East Asian Journal of Multidisciplinary Research, 2024)
Companies in competing in the era of globalization certainly must have qualified and competent human resources, therefore this study seeks to understand how proactive work behavior, organizational climate, and employee engagement impact employee performance at PT Sucofindo's Surabaya Branch. This study employs a quantitative approach, measuring variables through the use of a Likert scale. The sampling was carried out using a non-probability method with a purposive sampling approach, yielding a sample of 92 respondents. A Partial Least Squares (PLS) approach was used to evaluate validity, reliability, the structural model, and to test the hypotheses. The research findings indicate that proactive work behavior, organizational climate, and employee engagement each have a contribute and significant impact on employee performance at PT Sucofindo Surabaya Branch.